Fatigue analysis of thin AlMgSi welded joints under constant and variable amplitude block loadings - Pinho-da-Cruz, J. A. M. (2003)
This paper reports the fatigue behaviour of thin AlMgSi1 aluminium alloy weldments and the improvement in fatigue strength due to post-weld treatments. Several fatigue tests were performed using two distinct types of thin welded joints, T and single lap, manufactured using a 6xxx series aluminium alloy, and the efficiency of fatigue life improvement techniques, such as post-weld heat treatment and weld toe's burr dressing, was studied. Both the post-weld heat treatment and the burr dressing produced a fatigue strength improvement. This fact is discussed, for both geometries, in the context of the initiation and propagation phases contribution to total fatigue life. Finally, several fatigue tests were performed under variable amplitude block loading using T6 post-weld heat-treated single lap joints, and the correspondent fatigue lives were compared with the predictions of Miner's rule.